2017
DOI: 10.1590/1980-5373-mr-2016-0786
|View full text |Cite
|
Sign up to set email alerts
|

Thickness Dependent Structural and Electrical Properties of Magnetron Sputtered Nanostructured CrN Thin Films

Abstract: In the present work, we have investigated the structural and electrical properties of CrN thin films for a thickness t in the 30-220 nm range, grown on Si (100) substrates. The CrN/Si (100) films exhibits a structural transition from hexagonal phase (β-Cr 2 N) to cubic phase (CrN) with the increasing in film thickness, the change in structural transition is attributed to the decrease of film-substrate interfacial strain. From electrical resistivity measurements, the thickness of 150 nm CrN/Si (100) film shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Through Gaussian fitting analysis, the peaks at 282.97 eV, 284.50 eV and 285.51 eV correspond to CeCr (1st peak) and CeN bonds. According to Ye et al [30], the CeN bond is composed of sp 2 CeN and sp 3 CeN. This indicates that the CeN binding is strongly formed in the CreN coatings after incorporation of carbon atoms and confirms the coexistence of chromium nitride, carbide and carbonitride phases in the CreN system at high annealing temperature as shown with XRD analysis.…”
Section: Crystalline Structurementioning
confidence: 69%
See 1 more Smart Citation
“…Through Gaussian fitting analysis, the peaks at 282.97 eV, 284.50 eV and 285.51 eV correspond to CeCr (1st peak) and CeN bonds. According to Ye et al [30], the CeN bond is composed of sp 2 CeN and sp 3 CeN. This indicates that the CeN binding is strongly formed in the CreN coatings after incorporation of carbon atoms and confirms the coexistence of chromium nitride, carbide and carbonitride phases in the CreN system at high annealing temperature as shown with XRD analysis.…”
Section: Crystalline Structurementioning
confidence: 69%
“…Chromium thin films with exclusive super saturationed metalloid elements such as carbon or nitrogen have received wide technological interest due to their remarkable performance, such as high hardness, high elasticity modulus, good wear resistance and chemical stability under extreme conditions [1][2][3][4]. Nowadays, the most commonly used PVD coatings are chromium nitrides [5] and carbides [6].…”
Section: Introductionmentioning
confidence: 99%
“…Among the sputtered nitride films, vanadium nitrides offer excellent properties and present high corrosive resistance against aggressive media, and good oxidation resistance in ambient air at high temperature [3][4][5][6]. In addition, the VeN films were known to show a decrease in the friction coefficient with an increase in temperature due to the formation and melting of V 2 O 5 on the wear track during friction process [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Chromium nitride (CrN), as a typical transition metal nitride with outstanding mechanical performance, thermal properties, antioxidation behavior, and low magnetoresistance, has attracted much interest in applications of hard protective coatings, diffusion barriers, and thermoelectric and temperature sensors materials. In the past few decades, the vacuum method has been a major way to fabricate CrN thin films, where the nitrogen concentration in the films was controlled with the different nitrogen partial pressures used. It had found that the structural, magnetic, and electronic properties of CrN were sensitive to N component. …”
Section: Introductionmentioning
confidence: 99%